That's desire - Here we are EP - Tillmans, Wolfgang 1968- (Fragile, 2016)
That’s Desire/Here We Are EP is a 12′’ vinyl and digital release by Fragile, Wolfgang Tillmans’ evolving band project that spans from early recordings in 1986 with Bert Leßmann to a full band ensemble made up of a group of musicians in New York in 2016. The double A-side EP opens with That’s Desire, a collaboration with the New York rapper Ash B. The song evokes associations with DFA, DAF and a queer Talking Heads. In a spontaneous action Ash B. takes over the mic and raps over Tillmans’ heartfelt lyrics, originally written in 1985, combined with a funky bass line by Thomas Roach. The experiment results in a driving indie-dance sensation about the pleasure and pain of getting lost in one’s own desire. While Tillmans and Ash B. have their own individual take on their desires, the song’s arrangement and energy unifies them. Fast Lane, recorded in 1986 with Leßmann, captures the young alias of Tillmans – struggling with recurring issues of his time and apprehension of teenage growing pains in a punky attitude. In Anderes Osterlied, Fragile recreates a Protestant church song from the 1970s. Here We Are is a melancholic pop song about moments of stillness and drifting – moments to allow observance of everything around and finding diversion in simple things. More specifically, Naive Me directly reflects on the aftermath of Britain’s EU Referendum - contemplating personal illusion, the failures of ideology, and the hope for a better future. Warm Star, the last song of the EP, is a new wave inspired rock song that Tillmans initially created in collaboration with Juan Pablo Echeverri in Porto in 2016. In the tradition of German New Wave (NDW) songs, lyrically switching between German and English, the song